Lofting - Day, Arno N. (The boatbuilding video series., 2010)
"In this 10 hour set of videos you see Maine Master Boatbuilder Arno Day at work as he lofts the 24 ft. falmouth cutter "Seraffyn of Victoria." Designed by noted West Coast designer/builder Lyle Hess. Seraffyn was made famous by Lynn and Larry Pardy sailing her around the world. Lofting is the process by which a builder draws the design of a boat full size, correcting the errors and fairing the humps and hollows in the skin of the boat before he builds. Correct lofting makes the boat hydrodynamically sound. Arno demonstrates clearly the types of problems that come up and how to solve them. According to Arno, "Lofting completely saves you a lot of time in the shop. You're more accurate and the boat goes together easier." These videos give you the confidence to know you can do it."--Distributor's website.